Study of the Dynamic of Interregional Dual-System Electric Train of JSC "Kryukov Car-Building Company" - Myamlin, Serhiy V.; Prikhod'ko, Vladimir I.; Zhizhko, Viktoriya V.; Duzik, Vadym M. (Department of Railway Vehicles, Aircraft and Ships, BME Section of Rolling Stock, SSME, Budapest, Hungary, 2013)
EN: The purpose of this study is a theoretical evaluation of dynamic parameters of the head and the intermediate dual-system electric interregional train of JSC "Kryukov car-building company" throughout the range of operating speeds. The simulation uses a computer program «DYNRAIL», developed in Dnepropetrovsk National University of Railway Transport (DNURT). A results of the theoretical studies of dynamic loading of the head and Intermediate cars of dual- system interregional electric train it's received a confirmation of design speed, which is 200 km/h.

UK: Метою даного дослідження є теоретична оцінка динамічних параметрів головного і проміжних вагонів в двосистемному міжрегіональному електропоїзді ВАТ «Крюківський вагонобудівний завод" в усьому діапазоні робочих швидкостей. Моделювання використовує комп'ютер програму «DYNRAIL», розроблену в Дніпропетровському національному університеті залізничного транспорту (ДНУЗТ.) Результати теоретичних досліджень динамічного навантаження головного і проміжних вагонів в двосистемному міжрегіональному електропоїзді отримали підтвердження для створення швидкості, що становить 200 км / год.

RU: Целью данного исследования является теоретическая оценка динамических параметров главного и промежуточных вагонов в двухсистемном межрегиональном электропоезде ПАО «Крюковский Вагоностроительный завод" во всем диапазоне рабочих скоростей. Моделирование использует компьютер программу «DYNRAIL», разработанную в Днепропетровском национальном университете железнодорожного транспорта (ДНУЖТ). Результаты теоретических исследований динамической нагрузки главного и промежуточных вагонов в двухсистемном межрегиональном электропоезде получили подтверждение для создания скорости, что составляет 200 км / ч.
Вивчення динаміки міжрегіонального двосистемного електропоїзду ВАТ «Крюківський вагонобудівний завод"
Изучение динамики межрегионального двухсистемного электропоезда ПАО «Крюковский вагоностроительный завод"
S. Myamlin: ORCID 0000-0002-7383-9304
Keywords: dynamic parameters; dual-system electric interregional train; design speed; simulation; динамічні параметри; двосистемний міжрегіональний електропоїзд; розрахункова швидкість; моделювання; динамические параметры; двухсистемный межрегиональный электропоезд; расчетная скорость; моделирование; КВВГ; НДІ РСК і ТС